Cases and materials on Nigerian law of evidence (Nigeria Macmillan Nigeria Ltd., 1992)
This is the first compilation of cases, material and commentaries on Nigerian law of evidence. The author sets out the facts and decisions in most of the important cases in every aspect of Nigerian law of evidence. Salient point in each of of such decisions are expertly highlighted, and critical commentaries as well as further references are supplied where necessary.
includes index
aau, 1/08/22
Loan
Keywords: Evidence(Law); Nigeria